2023
DOI: 10.7717/peerj.15180
|View full text |Cite
|
Sign up to set email alerts
|

miR-126 promotes M1 to M2 macrophage phenotype switching via VEGFA and KLF4

Abstract: Background Macrophage polarization and microRNA play crucial roles in the development of atherosclerosis (AS). The M1 macrophage phenotype contributes to the formation of plaques, while the M2 macrophage phenotype resolves inflammation and promotes tissue repair. MiR-126 has been found to play a role in regulating macrophage polarization in the context of AS. However, the exact mechanism of miR-126 requires further research. Methods The foam cell model was established by stimulating THP-1 with oxidized low-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…CREB5 and KLF13, which influence macrophage polarization, were highly expressed in the Ma1 cluster. The Kruppel-like Factor (KLF) family is vital for regulating macrophage-mediated inflammation ( 48 ). For example, KLF13 knockdown downregulates the expression of M1 macrophage-related factors induced by lipopolysaccharides ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…CREB5 and KLF13, which influence macrophage polarization, were highly expressed in the Ma1 cluster. The Kruppel-like Factor (KLF) family is vital for regulating macrophage-mediated inflammation ( 48 ). For example, KLF13 knockdown downregulates the expression of M1 macrophage-related factors induced by lipopolysaccharides ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this study assessed the presence of key regulatory miRNAs associated with immune response, angiogenesis, and osteogenesis within the EVs. Compared to CEVs, BEVs exhibited the reduced levels of miRNAs related to a pro-inflammatory response, such as miR-130a-3p [34], and significantly increased the levels of miRNAs related to anti-inflammatory response, including miR-16-5p [35], miR-17-5p [36], miR-21-5p [37], miR-29b-3p [38], miR-34a-5p [39], miR-126a-5p [40], miR-146a-5p [41], miR-150a-5p [42], miR-221-3p [43], and miR-222-3p [44]. The levels of pro-angiogenic miRNAs were dramatically enhanced in BEVs, including miR-16-5p [45], miR-17-5p [46], miR-20a-5p [47], miR-21-5p [48], miR-23a-3p [49], miR-26a-5p [50], miR-29b-3p [51], miR-126a-5p [52], miR-146a-5p [53], miR-150a-5p [54], miR-155a-5p [55], miR-204-5p [56], and miR-221-3p [57].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that high levels of CD36 expression are associated with M2-type MAMs in ltration within tumors, leading to highly immunosuppressive tumor microenvironments [28]. Additionally, miR-126 promotes the transition from M1 to M2 macrophage phenotypes via VEGFA and KLF4 [29]. Therefore, further exploration into the role of these HSRGs in shaping immune cell in ltration and tumor microenvironments is highly valuable.…”
Section: Discussionmentioning
confidence: 99%